Strengthening Farmers’ Skills in Sustainable Land Management in Marga Cinta Village, Moramo District, South Konawe Regency - Sahindomi Bana; La Ode Muhammad Erif; Ema Hermawati Garusu; Wa Ode Hastiani Fahidu; Wa Ode Nanang Trisna Dewi; Alfirman (Institut Teknologi dan Bisnis Asia Malang, 2026)
Purpose: Conventional farming practices that rely heavily on inorganic fertilizers have contributed to soil degradation and declining land productivity in many rural areas. This community service program was implemented to strengthen farmers’ capacity in adopting sustainable land-management practices that restore soil health and support long-term agricultural productivity. Method: The program employed contextual agricultural extension combined with Focus Group Discussions (FGDs) to explore farmers’ perceptions, challenges, and existing practices. This was followed by an intensive two-month coaching period involving weekly field visits, hands-on training, and collaborative development of Standard Operating Procedures (SOPs) and group action plans for sustainable land management. The final stage consisted of systematic monitoring and evaluation to assess skill acquisition, behavioral change, and adoption levels among partner farmer groups. Practical Applications: The program facilitated the joint production and application of organic fertilizer using locally available crop residues. This activity served as both a practical demonstration of sustainable nutrient management and an alternative to residue burning, which commonly contributes to soil degradation. Conclusion: Findings show that many farmers lacked knowledge regarding soil quality, particularly the role of organic matter in maintaining soil fertility. Through capacity building, hands-on training, and participatory learning, the program successfully enhanced farmers’ awareness, skills, and commitment to improving soil health. The results indicate that strengthened ecological literacy can support the transition toward more sustainable and productive farming systems within the partner community.